Implementing public involvement standards in cerebral palsy register research - Kerr, Claire; McConnell, Karen; Savage, Helen; Acheson, Monica (Frontiers in Rehabilitation Sciences, 2022)
Background: In 2018, the National Institute for Health Research launched Draft Standards for Public Involvement in Research. The Northern Ireland Cerebral Palsy Register (NICPR) was competitively selected as a ‘test-bed’ project to pilot the Draft Standards over a one-year period. Aim: This perspective paper aims to describe the NICPR’s experience of piloting the Draft Standards for Public Involvement in Research, highlighting successes and challenges. Method: Three of the six Draft Standards were piloted from April 2018 to April 2019: Standard 2 ‘working together’, Standard 4 ‘communications’ and Standard 5, ‘impact’. Results: Implementation of Standard 2 resulted in formation of a dedicated Public Involvement Group. Standard 4 was implemented by revision of the NICPR’s Privacy Notice and development of the NICPR website. Standard 5 was not implemented during the test-bed pilot period. Discussion: Benefits of use of the Draft Standards in cerebral palsy register research included development of relationships, improving quality, accessibility and relevance of NICPR materials, increasing skills and confidence, networking opportunities, advocating for others and feeling empowered to shape cerebral palsy research. Challenges included administrative issues, absence of dedicated and sustained funding, limitations in the availability and applicability of public involvement training and the time required for meaningful public involvement. Conclusions: Standards for Public Involvement provide a useful framework for structuring and embedding meaningful public involvement. Sustained, authentic public involvement in cerebral palsy register research ensures that people affected by the condition are empowered to engage, inform, develop and lead research that meets their needs.